VISUAL STUDENTS SKILL IN DRAWING TWO DIMENSIONAL IMAGINATIF - Nia Safitri; Sri Hartatik; Nafiah Nafiah; Muhammad Thamrin Hidayat (AL-ISHLAH: Jurnal Pendidikan, 2020)
This study aims to determine the profile of visual student skills in imaginative two-dimensional drawing. This study uses a qualitative method. The subjects of this study were students of Class IIA at SDN Jemur Wonosari 1/417 Surabaya, which were categorized based on learning styles. The instrument used to collect data in the form of a checklist of learning styles, documentation and interviews. Based on the results of imaginative drawing show subjects with visual learning styles are able to draw two-dimensional imaginative by using the elements of lines and colors well. The visual subject in the picture is already able to use straight lines, curved lines and zig-zag lines. The visual subject has also been able to project three-dimensional objects into two-dimensional images. Visual subjects look a lot using colors in drawing. The combination of primary, secondary and tertiary colors. In images, the dominant color used by visual subjects is primary colours. It can be concluded that children with visual learning styles have the characteristics of being neat, orderly, thorough and concerned with appearance, so this is in line with the results of images that look neat, harmonious and realistic.